ANALISIS PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI DI SMA NEGERI 1 DRIYOREJO GRESIK - CHOIRUL ANWAR (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study aims to find out about the use of evaluation tools and evaluation tools for the selection of accounting material of economic subject of XI grades of SMA Negeri 1 Driyorejo Gresik, feasibility evaluation tools are made ​​and students' response to the use of the evaluation tool. This research is a descriptive study using a quantitative approach. Data was collected using the method of documentation, interviews, review of expert and student questionnaire responses. The results showed that accounting teacher at SMA Negeri 1 Driyorejo Gresik more often use a subjective test techniques and is said to be worth about theoretical (qualitative) but the empirical (quantitative) is said to be worth about. From the analysis of student responses is known that a given problem is in conformity with the accounting teacher materials and learning objectives, the use of language that is easy, no instructions work on the problems and the adequacy of working time. Keywords: Tool, Evaluation, Accounting and SMA